Breast compression and reported pain during mammographic screening. Issue 2 (May 2020) - Moshina, N.; Sagstad, S.; Sebuødegård, S.; Waade, G.G.; Gran, E.; Music, J.; Hofvind, S.
Abstract: Introduction: We aimed to investigate the association between breast compression and experienced pain during mammographic screening. Methods: Using a questionnaire, we collected information on pain experienced during mammography from 1155 women screened in Akershus, February–March 2018, as a part of BreastScreen Norway. The questionnaire provided information on pain using a numeric rating scale (NRS, 0–10) and related factors. Data on compression force (Newton, N), pressure (kilopascal, kPa) and breast characteristics were extracted from the DICOM-header and a breast density software. Log-binomial regression was used to determine the relative risk (RR) of severe versus mild/moderate experienced pain associated with compression parameters, adjusting for breast characteristics and related factors. Results: Mean score of experienced pain was 2.2, whereas 6% of the women reported severe pain (≥7) during the examination. High body mass index (BMI) (≥27.3 kg/m 2 ) was associated with a higher RR of pain scores ≥7 (RR 1.86, 95%CI 1.02–3.36) compared to medium BMI (23.7–27.2 kg/m 2 ). Low compression pressure (4.0–10.2 kPa) was associated with a higher RR of severe pain (RR 2.93, 95%CI 1.39–6.20), compared with medium compression pressure (10.3–13.5 kPa) after adjusting for contact area, age, compressed breast thickness, volumetric breast density and BMI. The risk of severe versus mild/moderate pain (≥7 versus <7) decreased by 2% with increasing compression force (RR 0.98, 95%CI 0.97–1.00). Conclusion: Women reported low levels of pain during mammography. Further knowledge about factors affecting experienced pain is needed to personalize the examination to the individual woman. Implications for practice: Pain in shoulder(s) and/or neck prior to screening should be considered by the radiographers in a practical screening setting. A compression force of 100–140 N and pressure of 10.3–13.5 kPa are acceptable with respect to reported pain during mammography.